Philippine Open Pit Copper Operations: Enhancing Operational Efficiency through Value Chain Analysis - Cinco, Jesus Jr. C. (Philippine Management Review; Vol 21 (2014))
Analysis of a selected large-scale Philippine open pit copper operation’s value chain, specifically the grade control aspect, was undertaken to assess the potential of enhancing its operating efficiency. Over 5,200 copper assays from blast holes were processed to determine the average grade continuity along three dimensions. Results indicated that modification of the existing sampling pattern of blast holes can translate to enhanced operating efficiency without losing operating effectiveness. This modified pattern is expected to translate to a 73% reduction in total variable costs mainly attributed to lower sampling and analytical costs. A trade-off equivalent to an insignificant 5% average increase in grade variability expressed in semi-variance is anticipated with the modified sampling pattern. Potential savings of PHP5.1 to PHP8.1 million annually is possible for a 42,000 to 60,000-tonne per day operation at a 2.14 waste:ore ratio. These results provide an insight into the potential savings that may be generated if applied to large-scale Philippine metallic mining projects currently operating or under development. Furthermore, the gains in operating efficiency can translate to enhanced revenues for government.
Keywords: value chain analysis, operations management, blast hole spacing optimization, semi-variogram, Philippine copper mines